VD_FINDINFO ML / 2013 / 53 vom 19. Februar 2013 - VD Tribunal cantonal (2013)
MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE, DÉCISION, AUTORITÉ ADMINISTRATIVE, INTÉRÊT MORATOIRE | 102 al. 1 CO, 104 CO, 80 LP